2008
DOI: 10.1111/j.1365-2141.2008.07435.x
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral blood monocytes are responsible for γδ T cell activation induced by zoledronic acid through accumulation of IPP/DMAPP

Abstract: SummaryNitrogen-containing bisphosphonates indirectly activate Vc9Vd2 T cells through inhibition of farnesyl pyrophosphate synthase and intracellular accumulation of isopentenyl diphosphate (IPP) and dimethylallyl diphosphate (DMAPP), but the cells responsible for Vc9Vd2 T cell activation through IPP/DMAPP accumulation are unknown. Treatment of human peripheral blood mononuclear cells (PBMCs) with a pharmacologically relevant concentration of zoledronic acid induced accumulation of IPP/DMAPP selectively in mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

20
241
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 259 publications
(262 citation statements)
references
References 12 publications
20
241
1
Order By: Relevance
“…Thus, zoledronate rapidly accumulates in monocytes. However, a 2.5-fold increase in IFN-g (from 10 to 25 pg/ml) and a 2.1-fold expansion of Vd2 T cells within 7 d, induced by zoledronate-treated monocytes and reported in the same study (20), does not convincingly demonstrate the importance of monocytes as a source of IPP. Rather, results from our study emphasize the role of monocytes as a source of IL-18.…”
Section: Discussionmentioning
confidence: 52%
See 3 more Smart Citations
“…Thus, zoledronate rapidly accumulates in monocytes. However, a 2.5-fold increase in IFN-g (from 10 to 25 pg/ml) and a 2.1-fold expansion of Vd2 T cells within 7 d, induced by zoledronate-treated monocytes and reported in the same study (20), does not convincingly demonstrate the importance of monocytes as a source of IPP. Rather, results from our study emphasize the role of monocytes as a source of IL-18.…”
Section: Discussionmentioning
confidence: 52%
“…The potent response of gd T cells in the complete absence of accessory cells, including monocytes, suggested that gd T cells can also take up zoledronate and produce sufficient amounts of IPP, a property that previously was attributed to monocytes only (20). However, Moser and colleagues (47,48) demonstrated that activated gd T cells can differentiate and may acquire many features of accessory cells, including increased endocytic activity, which would be required to accumulate zoledronate and to produce IPP.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Monocytes and dendritic cells are known to activate PB Vg9 + T cells when they are induced to express high levels of IPP, for example, by zoledronate, an inhibitor of farnesyl pyrophosphate synthase (17,18). To determine whether other cellular components of the synovium also play a role in activating SF Vg9 + T cells, we focused on the role of Sfib, which are critically dependent upon the mevalonate pathway, suggesting that they may continuously produce the Vg9 + Ag IPP (8).…”
Section: Activation Of Sf Vg9 + T Cells In Vivo and In Vitromentioning
confidence: 99%